Landscape as language: a comparative study of selected works by Susan Howe and Daphne Marlatt - Imms, Rhiannon (2006)
This thesis explores the work of two contemporary women poets, one American, the other Canadian, looking particularly at questions of subjectivity and embodiment in relation to place and to history. Their work is considered in the contexts of American modernist poetry, for instance that of Wallace Stevens, William Carlos Williams and Charles Olson, and in the light of critical theorists such as Gilles Deleuze and Felix Guattari, Michel Foucault, Luce Irigaray and Helene Cixous. Modernist concerns with the materiality of the text, both as product of a capitalist economy and as visual object, are considered alongside postmodern aspects of language as processional and reflexive. The early work of each writer is discussed separately in Chapters One and Two, with selected later work in more direct comparison in Chapters Three and Four.